Screenprinting (Northbrook, Ill. Roland Collection, 1993)
The video concentrates on how screenprints are made. Topics covered include the basic equipment, stencils, direct photo emulsion, washing and preparing the mesh, applying the emulsion, exposing it in the print down frame with UV light and then washing out the unexposed areas, retouching and printing the next color, inks and bases for printing, racking and removal of the stencil and cleaning the screen.
VHS format.
Director, Gavin Nettleton ; writers / consultants, Gavin Nettleton, Terry Gravett.
Keywords: Screen process printing